Why has the taxing policy on sugar sweetened beverages not reduced their purchase in Iranian households? - Ghodsi, Delaram; Haghighian-Roudsari, Arezoo; Khoshfetrat, MohammadReza; Abdollah-PouriHosseini, Seyedeh Fatemeh; Babapour, Mitra; Esfarjani, Fatemeh; Ajami, Marjan; Zargaraan, Azizollaah; Mohammadi-Nasrabadi, Fatemeh (Frontiers in Nutrition, 2023)
Objective: This study aimed at analyzing the effectiveness of the policy of taxing Sugar-Sweetened Beverages (SSBs) on their purchases during the last decade in Iranian households. Methods: The present mixed method study was done in 2017 in four phases: 1) A meta-review the fiscal policies during the last decade, 2) Collecting existing data on soft drinks’ production, price, and household expenditure during the last decade, 3) Conducting 19 semi-structured interviews with key informants, and 4) Facilitating a national meeting to achieve a consensus on the recommendations and future implications. Results: Document reviews showed that based on the Permanent Provisions of National Development Plans of Iran, the Ministry of Health and Medical Education (MOHME) should announce the list of health threatening products to increase taxation for them. The government is allowed to impose taxes on domestically produced and imported SSBs. The average household expenditure on SSBs increased in the rural and urban households of Iran during 2006-2016 in spite of taxation. In the different key informants’ opinion, only value-added tax (VAT) was implemented among different fiscal policies, and the other parts, including tax and tolls were debated. Conclusion: The present research findings further proposed some suggestions for increasing the effectiveness of financial policies in reducing NCDs in Iran